A Role for Caenorhabditis elegans Importin IMA-2 in Germ Line and Embryonic Mitosis - Geles, Kenneth G. (The American Society for Cell Biology, 2002)
The importin α family of nuclear-cytoplasmic transport factors mediates the nuclear localization of proteins containing classical nuclear localization signals. Metazoan animals express multiple importin α proteins, suggesting their possible roles in cell differentiation and development. Adult Caenorhabditis elegans hermaphrodites express three importin α proteins, IMA-1, IMA-2, and IMA-3, each with a distinct expression and localization pattern. IMA-2 was expressed exclusively in germ line cells from the early embryonic through adult stages. The protein has a dynamic pattern of localization dependent on the stage of the cell cycle. In interphase germ cells and embryonic cells, IMA-2 is cytoplasmic and nuclear envelope associated, whereas in developing oocytes, the protein is cytoplasmic and intranuclear. During mitosis in germ line cells and embryos, IMA-2 surrounded the condensed chromosomes but was not directly associated with the mitotic spindle. The timing of IMA-2 nuclear localization suggested that the protein surrounded the chromosomes after fenestration of the nuclear envelope in prometaphase. Depletion of IMA-2 by RNA-mediated gene interference (RNAi) resulted in embryonic lethality and a terminal aneuploid phenotype. ima-2(RNAi) embryos have severe defects in nuclear envelope formation, accumulating nucleoporins and lamin in the cytoplasm. We conclude that IMA-2 is required for proper chromosome dynamics in germ line and early embryonic mitosis and is involved in nuclear envelope assembly at the conclusion of mitosis.